La diversité des systèmes de protection sociale en Amérique latine - Bruno Lautier (Revue de la Régulation)
This paper suggests a method to analyse Latin American social protection systems. These are characterized by a large diversity regarding expenditures (i.e. their level and purpose) and regarding institutional organisation. Furthermore, they are all quite complex. These items are analysed in the first part of the paper. The second part is dedicated to elucidate the reasons for the failure to elaborate typologies liable to theorise this diversity, whether derived from typologies constructed for European social protection systems, or constructed on a connection between social protection and political regimes. The third part presents a proposal for a method, which roots the analysis of social protection systems in social rights configurations. This proposal proceeds in two stages: on one hand, a definition and a classification of very diversified social rights; on the other hand, the presentation of the analysis per se, in terms of “configurations of rights”, whose heuristic potential is suggested.